Plant-herbivore assemblages under natural conditions are driven by plant size, not chemical defenses. (1st December 2016) - Castells, Eva; Morante, Maria; Saura-Mas, Sandra; Blasco-Moreno, Anabel
Abstract: Aims: Plant secondary metabolites have been traditionally recognized as key traits regulating plant-herbivore assemblages. However, the ecological relevance of secondary metabolites as resistance mechanisms in comparison to other plant attributes, including physical, morphological or ecological traits, has been recently questioned. We aim to evaluate the role of chemical defenses, plant size and the presence of insect competitors on driving the differences in herbivory damage under natural conditions. Methods: We performed a replicated field study on the herbivore community associated with four Senecio species ( S. lividus, S. vulgaris, S. inaequidens and S. pterophorus ) during a full-reproductive season in Montseny Natural Park (Catalonia, NE Spain). Pyrrolizidine alkaloids (PAs), the most characteristic chemical defenses of Senecio due to their toxic effects on herbivores, were analyzed by gas chromatography. Individual plant size was estimated by the number of flower heads produced over the entire reproductive season. We used linear mixed models to explore the relationships between total PA concentrations, plant size and herbivory levels. Important Findings: PA concentrations were not related to the natural guild of herbivores within any plant species or insect type. Moreover, no significant interactions were found between insect species sharing the same host plants. In contrast, herbivore abundance was positively related to plant size in S. vulgaris, S. lividus and S. inaequidens . We found no evidence that PAs confer an increased plant resistance against herbivores in Senecio . Our study supports the hypothesis that plant chemical defenses have a secondary role in determining plant-herbivore assemblages in comparison to other plant traits under the complexity of natural conditions.